Medical Manuscript: Serum Total Testosterone as a Prognostic Indicator in Male Patients With Terminal Cancer. (June 2016) - Kim, Se Won; Hwang, In Cheol; Ahn, Hee Kyung; Kyung, Sun Young; Ahn, Hong Yup
The role of total serum testosterone in the prognosis of terminal cancer is unclear. We retrospectively investigated the total serum testosterone level in 69 male patients with terminal cancer in a palliative care unit. The association between the serum testosterone level and survival was assessed using Cox proportional hazard model. The median value of serum total testosterone was 44.5 ng/dL, far lower than previously reported in patients with advanced cancer. Multivariate analysis revealed thrombocytopenia (adjusted hazard ratio [aHR], 2.68), hypoalbuminemia (aHR, 2.02), azotemia (aHR, 2.67), and lower serum testosterone level (aHR, 2.03) were significantly negatively prognostic of survival. Lower serum testosterone level was an independent unfavorable prognostic factor for life expectancy in male patients with terminal cancer.